Scalar Product of Vectors |
|
Popular Pages |
The scalar product of two vectors is preseted alog with questions and detailed solutions. Some of the formulas for vectors are also used.
Scalar Product of Vectors
\( \) \( \)\( \) \( \)
The scalar product (also called the dot product and inner product) of vectors \( \vec{A} \) and \( \vec{B} \) is written and defined as follows
For vectors given by their components: \( \vec{A} = < A_x , A_y, A_z > \) and \( \vec{B} = < B_x , B_y, B_z > \), the scalar product is given by \[ \vec{A} \cdot \vec{B} = A_x \cdot B_x + A_y \cdot B_y + A_z \cdot B_z \] Note that if \( \theta = 90^{\circ} \) , then \( \cos(\theta) = 0 \) We therefore we can state that: Two vectors, with magnitudes not equal to zero, are perpendicular if and only if their scalar product is equal to zero. The scalar product may also be used to find the cosine and therefore the angle between two vectors \[ \cos \theta = \dfrac{\vec{A} \cdot \vec{B}}{|\vec{A}| \cdot |\vec{B}|} \] Properties of the Scalar Product
1) \( \vec{A} \cdot \vec{B} = \vec{B} \cdot \vec{A} \)
Questions and Applications the Scalar Product
Question 1
Question 2
Question 3
Question 4
Solution to Question 4 A tangent to a circle at point \( B \) is perpendicular to segment \( BC \) where \( C \) is the center of the circle (see figure on the right). Any point \( M(x , y) \) on the tangent is such that the scalar product \( \vec{BM} \cdot \vec{BC} \) is equal to zero. Point \( C \) is the center of the circle and therefore the midpoint of \( A \) and \( B \) . Its coordinates are given by \( C ( \dfrac{1+(-2)}{2} \; , \; \dfrac{2 + (-2)}{2} ) = C(- \dfrac{1}{2} \; , \; 0) \) Vectors \( \vec{BM} \) and \( \vec{BC} \) are defined by points \( B \), \( M \) and \( C \) and their components are given by: \( \vec{BM} \; = \; < x - (-2) , y - (-2) > \; = \; < x + 2 , y + 2 > \) \( \vec{BC} \; = \; < - \dfrac{1}{2} - (-2) , 0 - (-2)> \; = \; < \dfrac{3}{2} , 2> \) We now use the fact that the scalar product is equal to zero. \( \vec{BM} \cdot \vec{BC} \; = \; (x + 2)\dfrac{3}{2} + (y + 2)(2) = 0 \) Expand and simplify to find the equation of the tangent. \( \dfrac{3}{2} x + 2 y = - 7 \)
Question 5
Solution to Question 5 Let L1 be the line with equation \( y = 2 x + 4 \) and line L2 the line with equation \( y = x + 3\). First find the point of intersection by solving the system of equations: \[ y = 2 x + 4 \text{ and } y = x + 3 \] The point of intersection is at \( (-1 , 2) \) We now find the y-intercepts of the two lines For line L1 the y-intercept is \( (0 , 4) \) and for L2 the y-intercept is \( (0 , 3) \) We now find two vectors V1 and V2 parallel to L1 and L2 respectively. \( \vec{V1} = < 0 - (-1) , 4 - 2 > = < 1 , 2 > \) \( \vec{V2} = < 0 - (-1) , 3 - 2 > = < 1 , 1 > \) We now calculate the angle \( \theta \) between the lines given by their equations. \( \theta = \arccos (\dfrac{\vec{V1} \cdot \vec{V2}}{\vec{V1} \cdot \vec{V2}}) \) The dot product \( \vec{V1} \cdot \vec{V2} \) is calculate using the coordinates \( \vec{V1} \cdot \vec{V2} = < 1 , 2 > \cdot < 1 , 1 > = 3 \) The magnitudes of \( \vec{V1} \) and \( \vec{V2} \) \( |\vec{V1}| = \sqrt{1^2 + 2^2} = \sqrt{5} \) \( |\vec{V2}| = \sqrt{1^2 + 1^2} = \sqrt{2} \) \( \theta = \arccos \left(\dfrac{3}{\sqrt{5} \sqrt{2}}\right) \approx 18.43^{\circ}\) Más referencias y enlaces
More To Explore
{ezoic-ad-1}
|